Successful treatment of thoracic myelopathy caused by spontaneous spinal epidural hematoma (SSEH) combined with calcification of the ligamentum flavum (CLF) by posterior percutaneous endoscopic surgery (PPES): A case report - Lisheng, Hou; Dong, Zhang; Xuedong, Bai; Jinglei, Shi; Shaokui, Nan; Tianjun, Gao; Feng, Ge; Qing, He (Frontiers in Surgery, 2023)
Study Design. A retrospective case report. Objective. To report a case who developed deteriorated paraplegia by spontaneous spinal epidural hematoma (SSEH) on the basis of calcification of ligamentum flavum (CLF) at T10-11 level, achieved full neurological recovery following posterior percutaneous endoscopic surgery (PPES). Summary of Background Data. Calcification of the ligamentum flavum (CLF) rarely occurs at thoracic spine and the symptom usually progresses slowly. Spontaneous spinal epidural hematoma (SSEH) is another rare spinal lesion that might progress rapidly and cause emergent severe spinal cord compression syndrome. Coexistence of SSEH and CLF at the same thoracic level was rarely reported in English literature. Methods. A 65-year-old man presented to our hospital with the complaint of sensorimotor loss on the lower limbs and dysfunction of bladder for one day after a progressive weakness and numbness of lower limbs for 3 months. MR examination found dorsal protruding mass at T10-11 level, while CT found the protruding mass contained scattered calcified deposits. The patient was diagnosed with thoracic CFL. Decompression via posterior percutaneous endoscopic surgery (PPES) was carried out to realize bilateral decompression through unilateral approach. Results. During the operation, the protruding mass was found composed by SSEH and CLF together. After operation, the patient’s neurological function recovered quickly. One week later, the patient could walk by himself. 3 months later, complete neurological function recovered. Conclusion. SSEH could develop on the basis of CFL at thoracic level and cause serious neurological dysfunction. PPES might be an advisable method to remove CFL and evacuate SSEH with good clinical results.